2011
DOI: 10.3851/imp1982
|View full text |Cite
|
Sign up to set email alerts
|

HBV Genotypes: Relevance to Natural History, Pathogenesis and Treatment of Chronic Hepatitis B

Abstract: Although chronic HBV infection is the leading cause of chronic liver disease and death worldwide, there are substantial differences in its clinical courses regarding prevalence, mode of transmission, characteristics of each phase, responses to antiviral therapy, and development of cirrhosis and hepatocellular carcinoma, according to geographical areas (Asia versus Western Europe and North America versus Africa). Furthermore, the clinical course in infected individuals depends on a complex interplay among vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(142 citation statements)
references
References 170 publications
7
125
0
7
Order By: Relevance
“…We found that the prevalence of genotype C was significantly higher among patients with HCC than those without liver cancer. In fact, several studies reported that genotype C was related to a higher risk of HCC development as compared to genotype B, although such association was not confirmed by other studies (Kim et al, 2011). Additionally, we found significantly higher frequencies of A1762T/G1764A and T1753A/G/C mutations in the HCC group than in controls, which are consistent with previous reports (Chen et al, 2008;Yuen et al, 2008).…”
Section: Discussionsupporting
confidence: 62%
“…We found that the prevalence of genotype C was significantly higher among patients with HCC than those without liver cancer. In fact, several studies reported that genotype C was related to a higher risk of HCC development as compared to genotype B, although such association was not confirmed by other studies (Kim et al, 2011). Additionally, we found significantly higher frequencies of A1762T/G1764A and T1753A/G/C mutations in the HCC group than in controls, which are consistent with previous reports (Chen et al, 2008;Yuen et al, 2008).…”
Section: Discussionsupporting
confidence: 62%
“…In a portion of patients with chronic HBV infections who develop HbeAg seroconversion, normal serum ALT levels, HbeAg loss and anti HbeAb development and undetectable HBV DNA levels (inactive phase) are achieved. In some patients, HBV replication continues despite a negative Hbe Ag and increased ALT levels and moderate or advanced changes in hepatic histology are found (reactivation phase) as a result of mutations developing in the precore or basal core promoter regions of the virus 8,9 . Precore and basal core promoter mutations are frequently observed in HBV genotype D variants and cause to Hbe ag negative chronic HBV infection 8 .…”
Section: Resultsmentioning
confidence: 99%
“…B1 Japonya'da, B2-B5 Doğu Asya'da, B6 Kuzey Kutbunda yaşayan popülasyonda (örneğin Alaska, Kanada'nın kuzeyi, Grönland) daha sık gözlenmektedir. Genotip C ve subgenotip C1-C5 ise daha çok Doğu ve Güneydoğu Asya ülkele-rinde yayılım göstermektedir (8,9,22,23). Genotip/subgenotiplerin dünyadaki dağılımı Şekil 1'de belirtilmiştir (8).…”
Section: Hbv Genotip/subgenotipleriunclassified
“…Yeni tanımlanan genotip I, genotip A, C ve G'nin genotipik rekombinasyonu olarak ortaya çıkmış olup Vietnam ve Laos'tan izole edilmiştir. En yeni genotip olan genotip J, Japonya'nın Ryukyu adalarında tanımlanmış ve bu genotipin gibon/orangutan genotipleri ve insan genotip C'siyle yakın ilişkili olduğu bildirilmiştir (8,22). HBV genotip/subgenotiplerinin coğrafi dağılımları Tablo 1'de verilmiştir (8).…”
Section: Hbv Genotip/subgenotipleriunclassified
See 1 more Smart Citation